Development and Evaluation of a CO2 Capture System Using Hollow Fiber Membranes for Industrial Emissions Applications - Stephanie Arias-Lugo; Lucía Gómez-Coma; Guillermo Díaz-Sainz; Angel Irabien (Proceedings)
Membrane technology has emerged as a selective and efficient option for carbon dioxide (CO2) capture [...]